VIRTUAL REALITY IN EDUCATION: TRENDS AND ISSUES - Omieno, Kelvin Kabeti; Wabwoba, Franklin; Matoke, Nahason (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Computer-mediated learning is becoming an increasingly common form of education in institutions of higher learning (IHL). Many IHL in developing nations, such as Kenya, have greatly experienced an increase in demand for higher education.Â On the other hand, the ability to connect people with required sets of skills, regardless of their location in the world has been enabled by advances in information technology over the past 20 years. Use of virtual learning environment (VLE) has rapidly emerged as a very promising technology that will probably match the innovation of technologies such as multimedia/hypermedia. These VLEs have the potential to provide opportunities for active, flexible, and increasingly individualized learning experiences. It also explains virtual reality principle, describes the interactive educational environment, highlights the challenges higher education face in the traditional mode of delivery and discusses educational benefits of implementing virtual learning environments in IHL. The paper makes a number of recommendations for successful adoption of VLEs in higher education